Syirkah dalam Harta Bersama Suami Istri - Yureza Azzani (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
Abstract : This study is a discussion of normative law that examines the issue by referring to legal literature. The KHI regulates that after marriage, there is an automatic unification of joint assets obtained in the marriage bond for the wives and husbands. The provisions of Islamic law, especially when looking at the rules of classical fiqh books, do not recognize the concept of joint assets. In addition to the fact that there was no need for the concept of joint assets at that time, Islamic law also views that ownership of assets in marriage cannot occur automatically, because marriage cannot be the cause of the transfer of assets. Joint assets after marriage are classified into the type of syirkah contract. Keywords: syirkah, joint assets. Abstrak : Studi ini merupakan pembahasan hukum normatif yang mengkaji persoalan dengan merujuk pada literatur hukum. Dalam KHI diatur bahwa setelah perkawinan terjadi secara otomatif penyatuan harta bersama yang di dapat dalam ikatan perkawinan bagi para istri dan suami tersebut. Adapun ketentuan hukum islam terutama bila melihat pada aturan kitab fikih klasik, tidak mengenal adanya konsep harta bersama. Selain karena belum adanya dibutuhkan konsep harta bersama di masa itu, hukum islam juga memandang bahwa kepemilikan harta dalam pernikahan tidak bisa terjadi secara otomatis, sebab perkawinan tidak dapat menjadi sebab dari peralihan harta. Harta bersama setelah perkawinan digolongkan kedalam jenis akad syirkah. Kata Kunci : syirkah, harta bersama.